Visualization of liquid-solid interface morphologies in gallium subject to natural convection - Campbell, T.A.; Koster, J.N. (Journal of crystal growth, 1994)
Melting and solidification of pure gallium is studied using real-time radioscopy methods. Sharp contrast between melt and solid phases with a 3% density difference is illustrated. The interfacial shape reflects convective flow in the liquid phase. Comparisons are made between real-time non-intrusive X-ray observations and results gained from probing techniques and numerical simulations reported in the literature. Similar qualitative trends in temperature distribution, yet discrepancies in interfacial location and shape, are exhibited.